Neighborhood associations and community development: Differences in needs and strategies. Issue 5 (20th October 2018) - Anderson, Gary; Blair, Robert; Shirk, Josh
ABSTRACT: Neighborhood associations (NAs) help build social capital, enhance a sense of community, and elevate civic engagement. While urban researchers have studied NAs, there has been limited systematic observation of alliances of NAs. This research examines how neighborhood alliances (NALs) facilitate the creation and expansion of community capital that impact grassroots governance. We examine six NALs in Omaha, Nebraska that represent more than 120 active neighborhood associations. We find that participation in NALs is a good first step with respect to building social and political capital. Nevertheless, these NALs have yet to fully utilize this capital in the pursuit of resource sharing endeavors that cross multiple networks. More effort, therefore, is needed in the cultivation of the bridging and linking functions of community capital. For NALs to be construed as viable political actors, significant attention must be allotted to the development of generalized trust across NAL geographical boundaries.